Comparing the Effectiveness of Traditional and Alternative Baits in Prince Edward Island, Canada Lobster Fishery - Patanasatienkul, Thitiwan; Delphino, Marina K. V. C.; Thakur, Krishna K. (Frontiers in Marine Science, 2020)
The American lobster (Homarus americanus) fishery is an economically important commercial activity in Prince Edward Island (PEI), Canada. This fishery requires substantial amounts of bait, resulting in an emerging conservation challenge. To address this issue, an alternative lobster bait, manufactured using fresh and process pelagic fish, and dehydrated fish, corresponding to 75% less fresh pelagic fish than traditional bait has been developed by Bait Masters Inc. The performance of the alternative bait compared to that of the traditional bait was evaluated in a field study. This field trial was conducted in eight lobster fishing bays around PEI, during the 2019 lobster fishing seasons. Bait effectiveness was assessed based on catch-per-unit-effort (total lobsters and number of legal-sized lobsters caught per trap), and the ability to produce a catch. An average of five lobsters per trap were caught for both alternative and traditional baits. The results showed that both lobster bait types performed equally well in all PEI lobster fishing areas studied. This indicates that the alternative bait is a viable replacement for traditional bait, allowing the lobster fishery industry to address the bait-species shortage and ongoing conservation challenge.